2018
DOI: 10.29252/nfsr.5.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Rheological Properties and Microstructure of Canola oil as Affected by Monoacylglycerols

Abstract: A B S T R A C T Background and Objectives:Canola oil is very low in saturated fatty acid (8 %), which makes it suitable for application as dressing for salad. Canola oil is liquid, thus its application in the production of margarine and shortening is limited. The present study provides information about the effects of monoacylglycerols (MAG) as the structuring agent on physical, microstructure and rheological properties of canola oil. Materials and Methods:Canola oil was added 0.5, 3.0 and 5.0% MAGs. Fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…4,40,59 One particular study on the application levels of monoacylglycerol at increased doses over 3 or 5% indicated that there was an increasing response in the relative solid fat contents, crystal segregation, and entire liquefactions. 70 These results were in agreement to the finding of Saadi et al 59 and Saadi et al, 40 particularly on the impacts of monoacylglycerol at low doses in exhibiting surface-active ingredients by stabilizing the emulsion bodies and reordering and rearranging the granular crystals into different crystal regimes involving symmetric and asymmetric crystal polymorphs. Recently, molecular distillation techniques have been widely applied in the production of monoacylglycerol.…”
Section: Methods In Glycerolysissupporting
confidence: 91%
“…4,40,59 One particular study on the application levels of monoacylglycerol at increased doses over 3 or 5% indicated that there was an increasing response in the relative solid fat contents, crystal segregation, and entire liquefactions. 70 These results were in agreement to the finding of Saadi et al 59 and Saadi et al, 40 particularly on the impacts of monoacylglycerol at low doses in exhibiting surface-active ingredients by stabilizing the emulsion bodies and reordering and rearranging the granular crystals into different crystal regimes involving symmetric and asymmetric crystal polymorphs. Recently, molecular distillation techniques have been widely applied in the production of monoacylglycerol.…”
Section: Methods In Glycerolysissupporting
confidence: 91%
“…Products containing monoacylglycerols showed a higher storage modulus than loss modulus. Naderi et al (2018) studied the effect of monoacylglycerols on rheological properties of canola oil and reported that MAGs addition increased the viscosity, elasticity and complex moduli, and the complex viscosity. The products are suitable for the production of liquid margarine and shortenings.…”
Section: Rheologymentioning
confidence: 99%
“…DAG can also be used for making margarine. Saberi et al (2012) Naderi et al (2018) utilizing MAG in making liquid margarine and shortening from canola oil obtained products suitable for use in bakery. MAG from palm oil can also be mixed with chicken fat to get structured chicken fats that can be applied to produce soft tub margarine and Iranian vanaspati (Naderi et al, 2016)…”
Section: Shortening and Margarinementioning
confidence: 99%
See 1 more Smart Citation
“…From a technological point of view, the replacement of standard emulsifying agents by a multifunctional structured lipid would enhance both the stability of the emulsion and its performance. Rheological properties of the emulsion system are often treated as an indicator of the product quality just after preparation and after a few weeks of storage [12][13][14][15][16][17]. Dynamic and oscillatory rheological tests performed under controlled conditions provide crucial information about the emulsions stability and their response to various stimuli (temperature, shearing, oscillatory strain, pH, etc.)…”
Section: Introductionmentioning
confidence: 99%